Fluconazole-Pyridoxine Bis-Triazolium Compounds with Potent Activity against Pathogenic Bacteria and Fungi Including Their Biofilm-Embedded Forms - Marsel R. Garipov; Roman S. Pavelyev; Svetlana A. Lisovskaya; Elena V. Nikitina; Airat R. Kayumov; Alina E. Sabirova; Oksana V. Bondar; Albina G. Malanyeva; Alexander M. Aimaletdinov; Alfia G. Iksanova; Konstantin V. Balakin; Yurii G. Shtyrlin (Journal of Chemistry)
Two novel quaternary ammonium salts, bis-triazolium derivatives of fluconazole and pyridoxine, were synthesized by reaction of fluconazole with pyridoxine-based synthetic intermediates. The leading compound demonstrated pronounced antimycotic and antibacterial in vitro activity, comparable to or exceeding that of the reference antifungal (fluconazole, terbinafine) and antibacterial/antiseptic (miramistin, benzalkonium chloride) agents. In contrast to many antimicrobials, the leading compound was also active against biofilm-embedded staphylococci and Escherichia coli. While no biofilm structure destruction occurred, all compounds were able to diffuse into the matrix and reduce the number of colony-forming units by three orders of magnitude at 16 × MBC. The leading compound was significantly less toxic than miramistin and benzalkonium chloride and more toxic than the reference antifungal drugs. The obtained results make the described chemotype a promising starting point for the development of new broad-spectrum antimicrobial therapies with powerful effect on fungal and bacterial pathogens including their biofilm-embedded forms.